Perancangan Signage Lapangan Gasmin Kota Bandung - Soedewi, Sri; Murdowo, Djoko; Wulandari, Ratri; Yuniati, Arnanti Primiana; Gunawan, Putu Harry; Aditsania, Annisa; Adrin, Athaya Fatharani; Prabasworo, Bhanu (Visualita Jurnal Online Desain Komunikasi Visual, 2020)
The Gasmin Field is a public facility area located in Antapani, Bandung city. This field often uses for general community activities such as sports, gatherings, bazaars, ceremonies, and other activities. The condition of the environment around the Gasmin Field area is not well maintained. The absence of signage makes comfortless and makes it difficult for visitors when they want to find the target area. Therefore, signage and wayfinding designs are needed to make it easier to access locations around the Gasmin Field and increase visitor convenience. Design-based research use as a design method for Environmental Graphic Design (EGD) includes predesign, design, and post-design and data collection. Observations, interviews, and literature studies were carried out to obtain data and analyzed. The results of data analysis used to design signage and wayfinding in the Gasmin Field, Bandung City, West Java.